2019
DOI: 10.1088/1742-6596/1368/2/022056
|View full text |Cite
|
Sign up to set email alerts
|

Features of the construction of the registration scheme of optical images in an autonomous quantum magnetic field sensor

Abstract: The article describes the design of an autonomous quantum sensor for detecting variations of the magnetic field. The features of the regulation of the diffraction pattern of laser radiation using a ferrofluid cell placed in a uniform constant magnetic field are established. The optimal parameters for the design of the ferrofluid cell, magnetic fluid and laser radiation were determined. The experimental results of the study of the variation of the magnetic field from moving marine objects are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Our scenario calculations show that on the basis of modern technologies, including the use of nuclear power plants and hydrogen, with the coordinated actions of the world community, the problem of global warming can be solved in its minimum approximation [17][18][19][20][21][22][23][24]. We are modeling the system of social relations not only in its modern state, but for the human community along the entire path of its historical development.…”
Section: Resultsmentioning
confidence: 99%
“…Our scenario calculations show that on the basis of modern technologies, including the use of nuclear power plants and hydrogen, with the coordinated actions of the world community, the problem of global warming can be solved in its minimum approximation [17][18][19][20][21][22][23][24]. We are modeling the system of social relations not only in its modern state, but for the human community along the entire path of its historical development.…”
Section: Resultsmentioning
confidence: 99%
“…We also found that the photosensitivity of such contacts remains at a significant level even after the drying of the leaves, representing a certain practical interest [15][16][17][18][19][20][21][22][23][24][25].…”
Section: Resultsmentioning
confidence: 99%
“…Currently, there is a sharp increase in the technogenic load on the Earth's ecosystem [1][2][3][4][5][6][7][8]. There are many reasons for the increase in this load [7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%